The Effect of Fiscal Stress, Original Local Government Revenue and Capital Expenditures on Efficiency Ratio of Government Independence Performance - Ermatry Hariani; Retno Febriyastuti (Jurnal Ekonomi dan Studi Pembangunan, 2020)
The enactment of autonomy in Indonesia is to minimize the dependence of regional/local governments on the central government. In this case the regional/local government must be able to increase the source of revenue for the region. When fiscal stress is high, the government tends to explore the potential for tax revenues. The ability of an area to explore Original Local Government Revenue (PAD) will affect the development of the area. One of the important tasks of the Regional Government is to provide and build public infrastructure through the allocation of capital expenditure in the Regional Government Budget (APBD). Capital expenditure is the expenditure of the Regional Government which has the leverage to drive the economy. To measure the financial capacity of the local government is to analyze the financial ratios of APBD. This study use method of panel data, which is a combination of data time series (time series) and the data cross (cross section) in each province Indonesia 2016 - 2018. The method from this research use FEM (fixed effect model). The result shows that PAD has significant effect to efficiency ratio of government independence performance in each province in Indonesia. It means that high to low PAD has been influenced in ratio efficiency performance of independence. In this case the high and low fiscal ftress and capital expenditure do not have an influence on efficiency ratio of goverment independence performance.